Marketing Strategy of Msme Products Through the use of Digital Marketing in Duck Breakers in Pringapus District, Semarang District - Kustiyono Kustiyono (ProBisnis : Jurnal Manajemen, 2023)
Currently, digital marketing technology continues to experience development, and the benefits of using the internet are felt by its users. In fact, some people sense that they have a dependence on the internet, including the activities of duck breeders who are included in Micro, Small, and Medium Enterprises (SMEs) in utilizing information technology to run their business. This developing era encourages business people to always be able to follow digital trends. Transformations in the world of technology towards digitization have changed the way businesses work to be able to adapt faster to these developments. The presence of social media has now become a trend in conducting marketing communications. Social media including Google Business is an online media, where users can easily participate, share and provide information including blogs, social networks, wikis, and forums. Blogs, social networks, and these are the most common forms of social media used by people around the world. This type of research is descriptive research. The approach used is a qualitative approach and a conceptual approach. The source of data used is secondary data. Data analysis was carried out in a qualitative descriptive manner. Conclusions were drawn using the deductive method, namely concluding from general to specific, especially those related to the research topic, namely the Marketing Strategy for MSME Products through the Use of Digital Marketing for Bebek Bebek breeders in Pringapus District. This research resulted in findings on the importance of the role of digital marketing through Whatsapp, Instagram, and Shopee for current business development. With the concept of digital marketing, the form of promotion that is carried out is no longer a one-way scheme but has become a two-way relationship. This two-way relationship allows the presence of good interaction and is not hindered by distance and time between entrepreneurs and consumers. From the consumer's point of view, the use of the internet in fulfilling their daily needs provides many advantages and conveniences. Ease of product search, efficiency to discounted promos. Business actors who can apply digital marketing make the market grow and the products offered become more varied. However, there are still many micro-entrepreneurs who close themselves to development. They are still reluctant to do digital marketing where businesses only sell their products to consumers who are around or waiting for consumers who happen to pass through their market area. Running a business by utilizing internet access and conducting digital marketing through social media, websites or other e-commerce applications is a definite step and must be mastered for businesses to connect with customers and potential customers more quickly and easily. Market updates such as digital marketing are an important innovation for MSMEs to maintain their business. Apart from surviving the situation. In a pandemic like today, digital marketing is also one of the factors that can determine the success of competition in free trade.